الحركة التجديدية في النثر العراقي بين الخمسينيات والستينيات (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
ظهرت في العراق المؤلفات الأولى للخطة التجديديّة في منتصف عام 1950 في مرحلة ما قبل الأزمة الثورية، عندما أخضع النظام الإقطاعي الكلي السياسة الداخلية والخارجية للعراق لصالح الدوائر العدوانية والتكتلات الإمبريالية والاحتكارات الأجنبية، وعزل نفسه كلياً عن الشعب. إن التخفيف البطيء في حياة الإصلاحات الاجتماعية والاقتصادية المقبولة بعد عام 1950 والانقلابات السياسية التي هزت الدولة والتنكيل والاضطهاد الشعبي العام وفشل القوى التقدمية, قد أشعل وسط الأدباء الشباب المزاج الثوري التمردي وقد نشأ هذا المزاج في دوائر المثقفين العراقيين حتى قبل أعوام ثورة 1958. إن النظريات الجديدة للغة الشعرية التي صنعها الشعراء العراقيون مثل بدر شاكر السياب ونازك الملائكة وعبد الوهاب البياتي وغيرهم, قد ولدت لدى الشباب الثائر طموحا ورغبة في البحث عن أشكال جديدة للتفتيش, الذي أدى بالنتيجة إلى إبداع أو تجديدات شكلية, كذلك بحث الناثرون عن وسائل وطرق جديدة للتعبير الفني, تلبي حاجة الحداثة وتتوافق مع روح العصر الحديث. The first publications in modernism appeared in mid 1950, before the revolutionary crisis, when the totalistic feudal system subdued internal and external policies in Iraq to aggressive circles, imperial blocs, and foreign monopolies, thus isolating itself from the people. The slow move towards the social and economic reformation which was acceptable after 1950, the political coups which shook the countries, the social aggression and oppression against the people, as well as failure of the progressive forces, all stimulated the rebellious spirit among the young writers. This was clearly noticed among educated Iraqis, even before 1958 revolution. The modern theories in poetic language, which the Iraqi poets like Bader Al-Sayaab, Nazek Al-Malaikah, AbdAl-Wahab Al-Bayati, and others had emerged with the rebellious youth. This led to creativity and modernization in form. This is how the revolutionists looked for methods and new ways for artistic expression, which meet the needs for modernism and suits the spirit of the modern age.